2022
DOI: 10.1177/09722629221081915
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Relevance of Business Environment for Financial Performance: The Case of Asian Non-Banking Microfinance Institutions

Abstract: Microfinance aims at providing productive loans to deprived segments of society that helps in poverty eradication. Existing studies ignore some essential factors of business environment, which can influence the performance of microfinance institutions. We have collected data from the Doing Business project of the World Bank and audited financial statements of 52 Asian non-banking microfinance institutions for the period of 2012–2016. This study has employed system method of moments (GMM) technique with xtabond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…This might be a result of MFIs using distinct lending strategies, like group lending, to outperform traditional lending institutions in terms of debt recovery. It has been observed that various business environmental factors, including obtaining credit, safeguarding small investors, and paying taxes, have a substantial consequence on the financial performance of specific institutions (Farooq et al, 2022). Group lending reduces the possibility of morally hazardous behavior and unfavorable selection.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…This might be a result of MFIs using distinct lending strategies, like group lending, to outperform traditional lending institutions in terms of debt recovery. It has been observed that various business environmental factors, including obtaining credit, safeguarding small investors, and paying taxes, have a substantial consequence on the financial performance of specific institutions (Farooq et al, 2022). Group lending reduces the possibility of morally hazardous behavior and unfavorable selection.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Navajas et al [15] also argue that unsustainable MFPs cannot help the poor continuously because they generally disappear in the long run. In the field of microfinance, profitability and sustainability/self-sufficiency are usually measured with the help of accounting-based indicators such as; OSS, Financial Self-Sufficiency (FSS), Returns on Equity (ROE), and Returns on Assets (ROA) [46,[62][63][64][65][66][67][68]. These indicators are also helpful in investigating the financial viability of the MFPs [69, pg.49].…”
Section: Operational Self-sufficiencymentioning
confidence: 99%
“…The sustainability of MFPs starts with OSS, where the operating costs of the institutions are covered regardless of the revenue sources [73]. The expression used to calculate OSS ratio can be described as follow [68]:…”
Section: Operational Self-sufficiencymentioning
confidence: 99%